Preoperative Nutritional Status Contributes to the Development of Neutropenia Event in Patients With Gastric Cancer Receiving CAPEOX Adjuvant Chemotherapy - Xiao, Ai Tang; Tong, Yi Xin; Xu, Xiang Shang; Zhou, Yi; Zhang, Sheng (Frontiers in Oncology, 2020)
Purpose: The aim of this study is to evaluate the risk factors for ≥ grade 3 neutropenia in gastric cancer patients receiving postoperative adjuvant chemotherapy. Methods: This is a retrospective study from a single tertiary referral hospital. Patients diagnosed with gastric cancer who met the inclusion criteria were included in this study. Baseline and clinicopathological characteristics of the patients were collected. Patients were followed-up for 12 months and the incidence of neutropenia were recorded. Factors associated with neutropenia of chemotherapy in cycle 1 were investigated. Results: A total of 202 patients with gastric cancer were included. All patients received oxaliplatin plus oral capecitabine (CAPEOX) as the adjuvant chemotherapy. The incidence of ≥ grade 3 neutropenia is 11.9% (24/202) in cycle 1 among all patients. In multivariate analysis, independent risk factors for ≥ grade 3 neutropenia were serum prealbumin level (p = 0.041), prognostic nutritional index (PNI) (p = 0.049) and pre-cycle neutrophil count (p = 0.007). Conclusions: Our findings for the first time showed that nutritional parameter as prealbumin level and PNI are independent risk factors for neutropenia in gastric cancer patients receiving adjuvant chemotherapy. This may provide evidence for further investigation on prophylaxis use of granulocyte colony-stimulating factor in selected high-risk patients to prevent sever neutropenia in cycle 1 of adjuvant chemotherapy.